Westonci.ca is your go-to source for answers, with a community ready to provide accurate and timely information. Explore thousands of questions and answers from knowledgeable experts in various fields on our Q&A platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Answer:
[tex]y=\frac{-1}{2} \sqrt[]{4x^2+4c_{1}^2} -c_{1}\ or \ \frac{1}{2} \sqrt[]{4x^2+4c_{1}^2} -c_{1}[/tex]
Step-by-step explanation:
As it is first order nonlinear ordinary differential equation
Let y(x) = x v(x)
2xy/(x²+y²)=2v/(v^2+1)
dy=xdv+vdx
dy/dx=d(dv/dx)+v
x(dv/dx)+v=(2v)/(v^2+1)
dv/dx=[(2v)/(v^2+1)-v]/x
[tex]\frac{dv}{dx}=\frac{-(v^2-1)v}{x(v^2+1)}[/tex]
[tex]\frac{v^2+1}{(v^2-1)v}dv=\frac{-1}{x}dx[/tex]
∫[tex]\frac{v^2+1}{(v^2-1)v}dv[/tex] = ∫[tex]\frac{-1}{x}dx[/tex]
u=v^2
du=2vdv
Left hand side:
∫[tex]\frac{v^2+1}{v(v^2-1)}dv[/tex]
=∫[tex]\frac{u+1}{2u(u-1)}du[/tex]
=[tex]\frac{1}{2}[/tex]∫[tex](\frac{2}{u-1} -\frac{1}{u} )du[/tex]
=[tex]ln(u-1)-\frac{ln(u)}{2} +c[/tex]
=[tex]ln(v^2-1)-\frac{ln(v^2)}{2}+c[/tex]
Right hand side:
[tex]=-ln(x)[/tex]
Solve for v:
[tex]v=-\frac{-c_{1}+\sqrt{c_{2}+4x^2 } }{2x} \ or \ \frac{-c_{1}+\sqrt{c_{2}+4x^2 } }{2x}\\[/tex]
[tex]y=\frac{-1}{2} \sqrt[]{4x^2+4c_{1}^2} -c_{1}\ or \ \frac{1}{2} \sqrt[]{4x^2+4c_{1}^2} -c_{1}[/tex]
Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.